149 Deutetrabenazine for the Treatment of Tardive Dyskinesia: Results From an Open-Label, Long-Term Study. (15th June 2018) - Anderson, Karen E.; Davis, Mat D.; Factor, Stewart A.; Hauser, Robert A.; Jarskog, L. Fredrik; Jimenez-Shahed, Joohi; Kumar, Rajeev; FRCPC,; Ochudlo, Stanislaw; Ondo, William G.; Fernandez, Hubert H.
Abstract: Introduction: Tardive dyskinesia (TD) is an involuntary movement disorder resulting from exposure to dopamine-receptor antagonists. In the 12-week ARM-TD and AIM-TD studies, deutetrabenazine demonstrated significant improvements in Abnormal Involuntary Movement Scale (AIMS) scores at Week 12 compared with placebo, and was generally well tolerated. Objective: To evaluate the efficacy and safety of long-term deutetrabenazine therapy in patients with TD. Methods: Patients with TD who completed the ARM-TD or AIM-TD studies were eligible to enter this open-label, single-arm, long-term safety study after they completed the 1-week washout period and final evaluation in the blinded portion of the trial. Efficacy endpoints included the change in AIMS score from baseline, and treatment success (defined as "much improved" or "very much improved") on the Clinical Global Impression of Change (CGIC) and Patient Global Impression of Change (PGIC). This analysis reports results up to Week 54. Results: 304 patients enrolled in the extension study. At Week 54, the mean (standard error) change in AIMS score was –5.1 (0.52). After 6 weeks of deutetrabenazine treatment, the proportion of patients who achieved treatment success was 58% per the CGIC and 53% per the PGIC, and by Week 54 was 72% per the CGIC and 59% per the PGIC, thus demonstrating maintenance or enhancement of benefit over time. Deutetrabenazine was well tolerated for up to 54 weeks, and compared with the ARM-TD and AIM-TD studies, no new safety signals were detected. Conclusions: 54 weeks of deutetrabenazine treatment was generally efficacious, safe, and well tolerated in patients with TD. Presented at: The American Psychiatric Association 2017 Annual Meeting; May 20–24, 2017; San Diego, California, USA. Funding Acknowledgements: This study was funded by Teva Pharmaceutical Industries, Petach Tikva, Israel.